Uncertainty Quantification for Eigensystem-Realization-Algorithm, A Class of Subspace System Identification - Lam, Xuan-Binh; Mevel, Laurent (IFAC Proceedings Volumes, 2011)
In Operational Modal Analysis, the modal parameters (natural frequencies, damping ratios and mode shapes), obtained from Stochastic Subspace Identification of structures, are subject to statistical uncertainty from ambient vibration measurements. It is hence neccessary to evaluate the confidence intervals of these obtained results. This paper will propose an algorithm that can efficiently estimate the uncertainty on modal parameters obtained from the Eigensystem-Realization-Algorithm (ERA). The algorithm is validated on a relevant industrial example.